Directional Temporal Relationship Between Hypertension and Non‐Alcoholic Fatty Liver Disease: A Cross‐Lagged Cohort Study - Jianmin Tang; Halengbieke Aheyeerke; Xuetong Ni; Tengrui Cao; Xuan Wang; Shuo Chen; Yumei Han; Linrun Kong; Xinghua Yang (The Journal of Clinical Hypertension)
ABSTRACT The temporal relationship between non‐alcoholic fatty liver disease (NAFLD) and hypertension (HTN) remains unclear despite their known association. Using data from the Beijing Health Management Cohort (BHMC) with a 5‐year follow‐up, we investigated these bidirectional links through Cox proportional hazards regression and a cross‐lagged panel model (CLPM), adjusting for confounders. Systolic/diastolic blood pressure (SBP/DBP) and hepatic steatosis index (HSI) were treated as continuous variables to enhance biological interpretability. Cox regression revealed that HTN increased the risk of NAFLD (hazard ratio [HR]: 1.15, 95% confidence interval [CI]: 1.01–1.30, p < 0.05) among participants without NAFLD at baseline, while NAFLD elevated the risk of HTN (HR: 1.11, 95% CI: 1.02–1.21, p < 0.05) among those without HTN at baseline. However, CLPM involving 7349 participants identified a unidirectional temporal relationship from HTN to NAFLD, regression coefficients βSBP2017→HSI2022: 0.036 (95% CI: 0.012, 0.059), βDBP2017→HSI2022: −0.044 (95% CI: −0.068, −0.020), both p < 0.05; but not from NAFLD to HTN, regression coefficients βHSI2017→SBP2022: 0.017 (95% CI: −0.003,0.037), βHSI2017→DBP2022:0.006 (95% CI: −0.016,0.028), both p > 0.05. Overall, our study demonstrates a unidirectional temporal association from HTN to NAFLD. However, a bidirectional relationship was also observed in individuals under 60 years and in those without central obesity. These findings highlight the importance of considering age and central obesity to manage HTN to reduce the risk of future NAFLD and to manage NAFLD to reduce the risk of future HTN.